GEE Estimators in Mixture Model with Varying Concentrations - Doronin, Oleksii; Maiboroda, Rostislav (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
We discuss semiparametric mixture model where some components are parametrized with common Euclidean parameter and others are fully unknown. We introduce GEE approach and adaptive GEE-based approach for parameter estimation. Proposed estimators are tested on simulated sample.